Desempenho de aparelho condicionador de ar no contexto da qualidade da energia elétrica - Carvalho, Bismarck Castillo (2002)
In the present days, researches and developments associated to Electrical Power Quality rise as major concems to both intemational and national communities. Amongst the various areas of interest emerge the studies related to the operation of large, médium and small electric appliances found in industrial, commercial and residential installations. This dissertation goes toward the investigation of the relationship between air conditioner devices and the electrical supply quality. Typical disturbances such as voltage distortion, voltage sag and swell, voltage oscillation and even interruptions are taken into account to a commercial type of device. Both experimental and computational approaches are used to study the overall equipment behavior and, the laboratoiy results are used to validate the time domain model implemented into the SABER simulator.